Formative assessment: improvement, immediacy and the edge for learning. Issue 1 (2nd January 2016) - Staunton, Mike; Dann, Chris
Abstract: Formative assessment is about strengthening student learning and can dramatically improve student achievement when it guides changes in day-to-day classroom practice. Any attempt to understand formative assessment must therefore be grounded in a notion of learning, which this paper approaches from a constructivist/experiential perspective. Importantly, for a teacher to genuinely know if a student is learning, the teacher needs to deeply question the learner so as to enter into a student's thinking. Such deep questioning needs to be on going, not one-off single recall questions. This is not something that can be done from the front of the classroom using traditional didactic type approaches or using the initiation–response–feedback–response–feedback (IRFRF) which relates to formative practices. It requires micro-questioning skills on a developmental process, so that such on-going questioning does not degenerate into a sequence of closed interrogative recall questions. Fine-grained analysis of the dialogue used to promote high-level thinking through a questioning scaffold for facilitating formative learning is proposed.